The Stories They Tell: Exploring Multicultural Education Through Refugee Student Narratives in Turkish Classrooms - Samar Al-Zoubi; Nasser Qudah; Fadi Al-Taani (Yayasan Adra Karima Hubbi, 2025)
Background. Turkey hosts one of the world’s largest populations of refugee children, yet multicultural education within Turkish public schools remains underdeveloped and inconsistently implemented. Refugee students often navigate classrooms marked by linguistic barriers, cultural misrecognition, and limited curricular representation. Purpose. This study explores how refugee students’ personal narratives can inform and enrich multicultural education practices in Turkish classrooms. Drawing on a qualitative narrative research design, the study engaged 18 refugee students from Syrian, Afghan, and Iraqi backgrounds across five urban public schools. Method. Data were collected through narrative interviews and classroom observations, then analyzed thematically to uncover how students perceive their identities, educational experiences, and interactions with peers and teachers. Results. Findings reveal that refugee students’ stories reflect both resilience and marginalization, highlighting gaps in teacher preparedness, inclusive pedagogy, and culturally responsive curriculum. At the same time, narratives uncovered opportunities for empathy, cross-cultural dialogue, and identity affirmation when student voices were acknowledged in meaningful ways. Conclusion. The study concludes that integrating refugee narratives into classroom discourse can serve as a transformative tool for multicultural education, fostering more inclusive and humanizing pedagogical environments.